Challenges and learning from the transcatheter aortic valve implantation team during the COVID-19 pandemic: a nurse's perspective. (2021) - Frame, Angela; Kainth, Gurdeep; Kammerling, Einat
Abstract : The COVID-19 pandemic has had a major impact on NHS resources, causing disruption to all elective procedures and affecting each stage of the patient journey. For patients with severe symptomatic aortic stenosis, there is a significant risk of clinical deterioration if left untreated. The risk of delay needs to be weighed against the risk of acquiring COVID-19 during an admission for a procedure. This has presented many challenges for the transcatheter aortic valve implantation team. When offering any procedures during 2020, NHS trusts had a responsibility to protect patients from exposure to COVID-19 through infection control measures and adapting to COVID-19 secure pathways. The aim was to prevent the spread of COVID-19, while performing planned care to high-risk patients where possible, to prevent clinical harm caused by delays. The authors' practice needed to set realistic targets for the care that could be safely delivered at each phase of the pandemic. Therefore, new considerations and methods needed to be applied at every stage of the patient journey, from the patient referrals on the waiting list to post-procedure discharge planning. This required a team-based approach throughout. Transcatheter aortic valve implantation clinical nurse specialists have played a fundamental role in the coordination of the ever-changing situation, implementing the new pathways and monitoring the patients on the waiting list. Nurses in this role are also often the first point of contact for patients and family. This experience presented an opportunity for innovation and learning from change. This article will discuss the challenges faced by the transcatheter aortic valve implantation team, the strategies used during the pandemic and the lessons that can be applied to future practice from the authors' experiences in one centre in London.